Religion and American politics: domestic and international contexts - Napierała, Paulina (International relations in Asia, Africa and the Americas, 2024)
"This book presents a broad international and interdisciplinary perspective on the role of religion in American politics (both domestic and international). The volume is a result of the cooperation between Jagiellonian University scholars and an international group of academics, including renowned American specialists, who study the interactions between religion and American politics. Coming not only from the USA, but also from Israel, Spain, Hungary, Poland and the Palestinian territories, they give readers a unique international perspective on how the US deals with issues on the intersection of religion and politics. The volume starts with discussing theoretical approaches used in the book and introduces the debate on the new conceptualizations of political science of religion. The following chapters focus on various religious influences in US politics, civil religion, legal issues, public attitudes and the role of Black churches"--